Korelasi kompetensi profesional, motivasi kerja, dan budaya organisasi sekolah dengan produktivitas kerja guru SMP/MTs se-Kecamatan Temon - Sarjiya Sarjiya; Mulyoto Mulyoto (Universitas Sarjanawiyata Tamansiswa, 2016)
This study aims to determine the correlation between: (1) teachers’ professional competence and teachers’ working productivity, (2) teachers’ working motivation and teachers’ working productivity, (3) school organizational culture and teachers’ working productivity, (4) teachers’ professional competence, teachers’ working motivation, and school organizational culture altogether and teachers’ working productivity. This research is a descriptive quantitative research a kind of correlational research. The study population was all SMP / MTs teachers in Temon subdistrict in Kulon Progo Regency, amounting to 119 teachers. The samples are 92 teachers who were taken by proportional cluster random sampling technique. Data were analyzed using correlation technique are simple, double, and partial. The results of the regression analysis on the significance level of 5% showed that: (l) there is a significant positive correlation between the professional competence of teachers in the teachers’ working productivity with the effective contribution of 39.4%. (2) there is a significant positive correlation with the productivity of teachers’ working motivation of teachers with the effective contribution of 12.8%. (3) there is a significant positive correlation between organizational culture of schools with teachers working productivity with the effective contribution of 9.8%., And (4) there is a significant positive correlation jointly between the professional competence of teachers, teachers’ working motivation, and organizational culture of the school with the teachers working productivity with the effective contribution 62.0%. This suggests that the three independent variables have a significant positive correlation of working productivity of teachers.